1990
DOI: 10.2307/3869097
|View full text |Cite
|
Sign up to set email alerts
|

Protein Import into and Sorting inside the Chloroplast Are Independent Processes

Abstract: Plastocyanin is a nuclear-encoded chloroplast thylakoid lumen protein that is synthesized in the cytoplasm with a large N-terminal extension (66 amino acids). Transport of plastocyanin involves two steps: import across the chloroplast envelope into the stroma, followed by transfer across the thylakoid membrane into the lumen. During transport the N-terminal extension is removed in two parts by two different processing proteases. In this study we examined the functions of the two cleaved parts, C1 and C2, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 24 publications
(44 reference statements)
1
36
0
Order By: Relevance
“…Thus, the transit peptide with a thylakoid-transfer domain may well be transported to lipid bilayers of the organelle surface, then the chloroplast-targeting domain forms a (partially) helical structure in the lipid environments. Supporting this interpretation, residues 1-43 of the plastocyanin transit peptide fused to mouse dihydrofolate reductase, which does not itself show a high affinity for lipid bilayers [14], could not be imported into chloroplasts; at least residues 1 -53 of the plastocyanin transit peptide were necessary to direct mouse dihydrofolate reductase into chloroplasts [7]. Plastocyanin with a deletion of residues 44 -64 of the transit peptide can still be imported, but in this case, the C-terminal hydrophobic residues in the thylakoid-transfer domain, Ah65 and Met66, remain intact and the following N-terminal region of the mature plastocyanin including Alal, Va13, Leu4, Leu5, etc., is also highly hydrophobic.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Thus, the transit peptide with a thylakoid-transfer domain may well be transported to lipid bilayers of the organelle surface, then the chloroplast-targeting domain forms a (partially) helical structure in the lipid environments. Supporting this interpretation, residues 1-43 of the plastocyanin transit peptide fused to mouse dihydrofolate reductase, which does not itself show a high affinity for lipid bilayers [14], could not be imported into chloroplasts; at least residues 1 -53 of the plastocyanin transit peptide were necessary to direct mouse dihydrofolate reductase into chloroplasts [7]. Plastocyanin with a deletion of residues 44 -64 of the transit peptide can still be imported, but in this case, the C-terminal hydrophobic residues in the thylakoid-transfer domain, Ah65 and Met66, remain intact and the following N-terminal region of the mature plastocyanin including Alal, Va13, Leu4, Leu5, etc., is also highly hydrophobic.…”
Section: Discussionmentioning
confidence: 67%
“…1) [6]. The detailed in vitro import studies, using deletion mutants of pPC, have revealed that a pPC derivative lacking residues 44 -64 of the transit peptide can be imported into isolated chloroplasts, while a deletion of residues 38 to 64 abolishes the ability of the pPC derivative to import plastocyanin but still leaves some ability to bind to the chloroplast surface [7]. It is also known that the processing of the pPC transit peptide takes place first around residue 40 in the stroma and after residue 66 (the end of the transit peptide) in the thylakoid lumen [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The transit signals, which are hydrophilic, basic and enriched in hydroxylated residues, are structurally and functionally equivalent to the presequences of imported stromal proteins (Ko and Cashmore, 1989;von Heijne et al, 1989;Hageman et al, 1990). In contrast, thylakoid transfer signals are strikingly similar in structural terms to signal sequences which direct the translocation of proteins across the endoplasmic reticulum and the bacterial plasma membrane (von Heijne et al, 1989).…”
mentioning
confidence: 99%
“…This complex import pathway can be broadly divided into two phases, the first of which involves the transport of a cytosolically synthesized precursor protein into the stroma, after which the stromal form is transported across the thylakoid membrane into the lumenal space (Hageman et al, 1986;James et al, 1989;Ko and Cashmore, 1989;Hageman et al, 1990). The two translocation events are directed by distinct signals in the presequences of lumenal proteins.…”
mentioning
confidence: 99%